2015
DOI: 10.3402/ijch.v74.26952
|View full text |Cite
|
Sign up to set email alerts
|

What can we talk about, in which language, in what way and with whom? Sami patients' experiences of language choice and cultural norms in mental health treatment

Abstract: BackgroundThe Sami in Norway have a legal right to receive health services adapted to Sami language and culture. This calls for a study of the significance of language choice and cultural norms in Sami patients’ encounters with mental health services.ObjectivesTo explore the significance of language and cultural norms in communication about mental health topics experienced by Sami patients receiving mental health treatment to enhance our understanding of linguistic and cultural adaptation of health services.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 20 publications
4
37
1
5
Order By: Relevance
“…As for the Sami, the level of fluency in Sami language necessary to be accepted as Sami-speaking has not been defined (21,28). In addition, findings in a previous study (12), as well as in the present study, indicate that Sami-speaking patients switch between languages depending on with whom they talk, and when talking about emotional issues. Bilingualism and the use of language switch in different situations may conceal language needs (42).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As for the Sami, the level of fluency in Sami language necessary to be accepted as Sami-speaking has not been defined (21,28). In addition, findings in a previous study (12), as well as in the present study, indicate that Sami-speaking patients switch between languages depending on with whom they talk, and when talking about emotional issues. Bilingualism and the use of language switch in different situations may conceal language needs (42).…”
Section: Discussionsupporting
confidence: 83%
“…This study concurs with findings in a previous study showing how Sami-speaking patients switch between Sami and Norwegian in therapy (12). This raises questions about the significance of language switch in therapy.…”
Section: Further Researchsupporting
confidence: 93%
See 1 more Smart Citation
“…Dagsvold et al. interviewed four bilingual care receivers with North Sami background in outpatient mental health in Norway, about their preferred language when receiving care, and they found that language choice was influenced by the language competence of both the care receiver and care provider. Dagsvold et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dagsvold et al. found that language choice influenced whom the care receiver talked to and what the care receiver talked about, and they highlighted that switching between Sami and Norwegian was a natural part of everyday life, and one participant said that it did not make any difference whether speaking Sami or Norwegian because of their ability to express themselves and to think clearly in both languages. Similar thoughts were not expressed by participants in our study, but some highlighted that whether care providers speak Swedish or South Sami was seen as secondary.…”
Section: Discussionmentioning
confidence: 99%